Rose K Lenses for Keratoconus - Alime Güneş; Anıl Kubaloğlu; Hüseyin Bayramlar (Türk Oftalmoloji Dergisi, 2012)
Pur po se: To report our results with Rose K contact lenses in patients with keratoconus. Ma te ri al and Met hod: Thirty one eyes of 17 patients with keratoconus were fitted with Rose K contact lens (CL) in the Cornea Department at the Ümraniye Training and Research Hospital between March 2011 and June 2011. The demographic characteristics, values of refraction, best spectacle-corrected visual acuity, corneal topography of patients, CL parameters and visual acuity with the CL were evaluated. Re sults: Thirty one eyes of 17 patients with keratoconus were fitted with Rose-K contact lenses. Seven patients were male and 10 patients were female, the mean age was 24.59±7.28 years. The mean spherical refractive power was -4.96±3.17 diopters (range: from -0.25 to -11.75) and mean cylinder was -3.47±1.44 diopters (range: from -1 to -6.5). The mean base curve of the lenses was 6.94 ± 0.49 mm and the mean power was -6.02±3.79 diopters. All patients were successfully fitted with the CL. Significant increase in visual acuity was obtained with Rose K lens compared to best-corrected spectacle visual acuity. Dis cus si on: Significant increase in visual acuity can be obtained with Rose K contact lenses in patients with keratoconus. The quality and the quantity of vision are far better with CL than with spectacle correction. (Turk J Ophthalmol 2012; 42: 88-90)